Utilizing islamic banking products to alleviate poverty in Nigeria (2012)
Although successive governments and international organisations have tried to address the issue of poverty, the effects of their strategies and programmes have not made much impact on the poor. There is a need to search for better ways or strategies of implementing poverty reduction programmes to make them more effective and sustainable. The paper, therefore, enumerates the causes of poverty and the attempts of the past governments in Nigeria to alleviate it. It discusses how Islamic banking products can be utilized to alleviate poverty. It is easy to empower the poor and alleviate poverty in an Islamic economy through the use of the Islamic banking products, Zakat (alms) and qard hasan (good loan). Creation of jobs for both skilled and unskilled workers in the country is possible through Islamic finance.